2020
DOI: 10.1515/rams-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Reinforced Bulk Metal Matrix Composites: Synthesis, Microstructure, and Properties

Abstract: This paper provides a critical review on the current status of graphene-reinforced metal matrix composites (GRMMCs) in an effort to guide future work on this topic. Metal matrix composites are preferred over other types of composites for their ability to meet engineering and structural demands. Graphene is considered an ideal reinforcement material for composites due to its unique structure and extraordinary physical, thermal, and electrical properties. Incorporating graphene as a reinforcement in metals is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 161 publications
(763 reference statements)
1
15
1
1
Order By: Relevance
“…Furthermore, the density of the composites is found to decrease with the increasing amount of GNPs due to an incremental decrease in the density of the Al matrix due to its replaced amount by GNPs. A similar trend in the density results was noticed in a previous study conducted on Al-Graphene composites [ 10 , 17 ]. For a deeper insight into the density behavior of the composites, relative density ( ) of the developed composites was determined using the actual or measured density ( ) and the theoretical density values ( ) as indicated in the below Equation [ 31 ].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, the density of the composites is found to decrease with the increasing amount of GNPs due to an incremental decrease in the density of the Al matrix due to its replaced amount by GNPs. A similar trend in the density results was noticed in a previous study conducted on Al-Graphene composites [ 10 , 17 ]. For a deeper insight into the density behavior of the composites, relative density ( ) of the developed composites was determined using the actual or measured density ( ) and the theoretical density values ( ) as indicated in the below Equation [ 31 ].…”
Section: Resultssupporting
confidence: 89%
“…It can be observed that the hardness and Young’s modulus of Al-Si 3 N 4 -GNPs composites increase with increasing concentration of GNPs. Such behavior is attributed to the presence of GNPs having a positive influence in improving the mechanical properties of pure Al [ 6 , 17 ]. Besides, the presence of hard crystalline Si 3 N 4 nanoparticles has also contributed to improving the hardness of the pure Al matrix [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it was also found that anisotropic bridge microstructure can regulate the morphology and biological function of Schwann cells [13]. The synthetic matrix showed extraordinary physical properties to meet microstructural demands [14]. Synthetic hydrogel-based materials with the micro-groove structure on the surface can also effectively regulate the migration and oriented growth of Schwann cells [15].…”
Section: Introductionmentioning
confidence: 99%